Harry's farewell : interpreting and teaching the Truman presidency - Kirkendall, Richard Stewart, 1928- (Columbia : University of Missouri Press, 2004)
"Harry's Farewell confronts the biggest issue of Truman historiography: the historical significance of Harry S. Truman's presidency. Exploring the subject from the point of view of Truman's Farewell Address of January 15, 1953, the book begins by describing the preparation of the address itself by the president and his closest advisers. In it, they challenged the negative view of his presidency that prevailed as he prepared to leave the White House. The book goes on to appraise the presidency in terms of the topics included in the address: the president and the people, the economy, civil rights, the bomb, Containment, Korea, and the end of the Cold War. Four essays follow that cover key topics that Truman did not mention in his speech: the Red Scare, women's rights, ethnicity, and the environment. The book ends with essays by two major Truman biographers who present their own interpretations of his historical significance."--Jacket.
Harry's farewell address and the historical significance of the Truman presidency / Richard S. Kirkendall -- The politics of democracy : Harry S. Truman and the American people / Alonzo L. Hamby -- Economic prosperity, security, and equality : Harry Truman's farewell claims and presidential achievements / Robert M. Collins -- Clutching at civil rights straws : a reappraisal of the Truman years and the struggle for African American citizenship / Carol Anderson -- President Harry S. Truman's farewell address and the atomic bomb : the high price of secrecy / Richard B. Frank -- Harry S. Truman, history, and internationalism : the 1953 farewell address and U.S. foreign relations / Mary Ann Heiss -- Truman and Korea : an assessment of presidential performance / William Stueck -- The Truman prophecy / Randall B. Woods -- "A very dangerous course" : Harry S. Truman and the red scare / Ellen Schrecker -- Behind the silences : challenges to the gender status quo during the Truman years / Susan M. Hartmann -- Harry Truman, immigration, and ethnicity at an imperial moment / Rachel Ida Buff -- A legacy in concrete : the Truman presidency transforms America's environment / Karl Brooks -- Using the farewell address to teach the Truman presidency / Jeff Gall -- Harry Truman : a biographer's perspective I / Robert H. Ferrell -- Harry Truman : a biographer's perspective II / Alonzo L. Hamby.
Includes index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Truman, Harry S., -- 1884-1972 -- Political and social views; Truman, Harry S., -- 1884-1972 -- Influence; Truman, Harry S., -- 1884-1972; United States -- Politics and government -- 1945-1953.; États-Unis -- Politique et gouvernement -- 1945-1953.; HISTORY; Influence (Literary, artistic, etc.); Political and social views; Politics and government; United States; Presidentschap; United States - General; Regions & Countries - Americas; History & Archaeology; 1945-1953